IN TEACHING LEARNING ACTIVITIES DURING PANDEMIC, STUDENT RESPONSE TO COMBINATION LEARNING POLICY (SDUA REJANG LEBONG CASE STUDY) - Gunawan, Guntur; Hadiwinarto; Johanes Sapri (Corolla International Conference, 2022)
The purpose of this study is to examine the responses of parents of students at the Aisyah Primary School (SDUA) Rejang Lebong to a mixture of learning policies from teaching and learning activities while accompanying their children to learn from home and face-to-face. The survey technique used was a google form filled out by the guardians of SDUA Rejang Lebong Regency students. The data gathering method is in the form of a questionnaire, and the questionnaire distribution will take place between February 11 and February 20, 2021. During the pandemic, 30 people were given questionnaires with 9 items concerning integrated learning in teaching and learning activities (KBM). According to the study results, 60 percent of parents of students think that their children’s learning outcomes through a mixture of online and face-to-face learning are good, while 40 percent disagree, then, in the percentage of responses from student guardians regarding working on teacher-assigned assignments via the internet, rendering youngsters inactive Because 56.7 percent agree and 43.3 percent disagree, it can be deduced that if pupils just use internet media, children will become more passive. Furthermore, guardians of students’ responses to the existence of combination learning can give children freedom in the learning process were overwhelmingly positive, with 80% agreeing and 20% disagreeing. It is clear that combination learning can give students more freedom in carrying out learning activities. The following number pertains to the student’s guardian’s response in working on each of their children’s assignments, and whether parents are constantly active in this, with 63.3 percent agreeing and 36.7 percent disagreeing, it is understandable that the teacher’s duty for his students must include his parents. Furthermore, parents’ responses to face-to-face learning are far more suitable than their responses to online learning, with 90 percent agreeing and 10% disagreeing. Furthermore, 56.7 percent agree and 43.3 percent disagree that holding learning activities in conjunction with face-to-face meetings improves student learning results, it is clear that learning in a group setting makes it more easier for pupils to absorb the topic and improves their learning outcomes. Furthermore, 60 percent of parents agreed and 40 percent disagreed that parents should be involved in completing the tasks assigned by the teacher, Then, in response to the question of whether combination learning can include children’s learning activities, 76.7 percent agreed, while the remaining 23.3 percent disagreed. Finally, when asked if combination learning can improve children’s discipline, 70 percent of parents agreed and 30 percent disagreed. As a result, it can be inferred that for the present, if just using the online system, most students cannot understand the content and neglect the chores assigned by the teacher, and most students are more passive in their work since individuals who do more work are parents. Another advantage is that when it is integrated with a faceto-face system, the teacher may present entire material, track students’ progress, and constantly push pupils to engage in the learning.